2018
DOI: 10.1051/0004-6361/201731669
|View full text |Cite
|
Sign up to set email alerts
|

Lyman-continuum leakage as dominant source of diffuse ionized gas in the Antennae galaxy

Abstract: The "Antennae Galaxy" (NGC 4038/39) is the closest major interacting galaxy system and therefore often taken as merger prototype. We present the first comprehensive integral field spectroscopic dataset of this system, observed with the MUSE instrument at the ESO VLT. We cover the two regions in this system which exhibit recent star-formation: the central galaxy interaction and a region near the tip of the southern tidal tail. In these fields, we detect H ii regions and diffuse ionized gas to unprecedented dept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 109 publications
2
59
2
Order By: Relevance
“…In other words, we find a "retired" RSFMS for the DIG component. As our study focuses on the regions ionized by hot/young stars, this result helps to understand the origin of the DIG at sub-kpc scales and agrees with Weilbacher et al (2018), where they found that the leaking UV photons from Hii regions can explain the ionization of the DIG. Our study cannot rule out the possibility that the hot old stars can ionize part of the DIG because we do not study the LINER-like ionized regions.…”
Section: The Stellar Mass Density Versus Sfr Density Relation On Mad supporting
confidence: 85%
See 1 more Smart Citation
“…In other words, we find a "retired" RSFMS for the DIG component. As our study focuses on the regions ionized by hot/young stars, this result helps to understand the origin of the DIG at sub-kpc scales and agrees with Weilbacher et al (2018), where they found that the leaking UV photons from Hii regions can explain the ionization of the DIG. Our study cannot rule out the possibility that the hot old stars can ionize part of the DIG because we do not study the LINER-like ionized regions.…”
Section: The Stellar Mass Density Versus Sfr Density Relation On Mad supporting
confidence: 85%
“…This component can be pushed above the galactic disk by superbubbles created by supernova events (e.g., Wood et al 2010). Weilbacher et al (2018) recently found that the UV photons leaked by the Hii regions in the Antennae can explain the ionization of the DIG there.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, DIG can contribute 50% or more to the observed Hα flux of a galaxy (e.g., review by Haffner et al 2009). The origin of the ionizing photons producing the DIG is still debated, with some or indeed all of these photons originating from massive young stars (e.g., due to Lyman-continuum leakage from H II regions; Weilbacher et al 2018). For our purposes, the key issue is that the DIG emission is not necessarily co-spatial with the young stellar population powering the Hii regions (see, e.g., Kreckel et al 2016).…”
Section: Filtering Out Emission From Diffuse Ionized Gas (Dig)mentioning
confidence: 99%
“…NGC 4038/39 system is more massive and the TDG has a 15 kpc diameter whereas KUG 0200-096 TDG diame-ter is 2.5 kpc. Weilbacher et al (2018) identify multiple sub-clumps in the NGC 4038/39 TDG and detected multiple HII regions. In that sense, KUG 0200-096 TDG is morphologically more similar to BCDs, typically xBCDs (Drinkwater & Hardy 1991) and in contrast morphological properties of NGC 4038/39 TDG is comparable to a typical dwarf irregular galaxy (dIr).…”
Section: Formation Of Tdgs During Dwarf-dwarf Mergermentioning
confidence: 81%